Modernism and the culture of market society - Cooper, John Xiros 1944- (Cambridge University Press, 2004)
Many critics argue that the modernist avant-garde were always in opposition to the commercial values of market-driven society. For John Xiros Cooper, the avant-garde bears a more complex relation to capitalist culture than previously acknowledged. He argues that in their personal relationships, gender roles and sexual contacts, the modernist avant-garde epitomised the impact of capitalism on everyday life. Cooper shows how the new social, cultural and economic practices aimed to defend cultural values in a commercial age, but, in this task, modernism became the subject of a profound historical irony. Its own characterising techniques, styles and experiments, deployed to resist the new nihilism of the capitalist market, eventually became the preferred cultural style of the very market culture which the first modernists opposed. In this broad-ranging 2004 study John Xiros Cooper explores this provocative theme across a wide range of Modernist authors, including Joyce, Eliot, Stein and Barnes